MENINGKATKAN LITERASI DIGITAL ANAK MELALUI PROGRAM LES PRIVAT KOMPUTER DI DESA HILIZIHONO - Agung Prasetya Putra Sarumaha; Christ Mesti Dame Sihura; Haogozatulo Buulolo; Imel Kanis Wau; Kei Santrisca Manao; Putri Ceriani Halawa; Senidar Ndruru; Testan Ayu Duha; Wilson Sihura; Yohanes Rifaldo Laia; Yoseph Edision Gowasa; Melkana Damanik; Hasaziduhu Moho (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
This article discusses the implementation of the Community Service Program (KKN) in the form of private computer tutoring as an effort to improve the digital literacy of children in Hilizihono Village. In today's digital era, digital literacy skills are crucial for children to prepare them for future challenges. However, limited access to and knowledge of technology in rural areas is a major obstacle. Through this community service program, KKN students provided basic computer training to children in Hilizihono Village using interactive and fun learning methods. The program's implementation results showed significant improvements in basic computer understanding, software operation skills, and awareness of digital ethics and security. Despite facing several challenges such as limited infrastructure and devices, this program successfully had a positive impact on the village community. This article recommends the importance of continuing similar programs and multi-stakeholder collaboration to improve digital literacy comprehensively in rural areas.